Polarization holographic recording in polymeric and liquid crystalline materials - Provenzano, Clementina; Cipparrone, Gabriella; Longeri, Marcello (My University, 2006)
Optical studies related to polarization holographic recording in photosensitive materials, as azo compounds, liquid crystals and polymeric mixtures, and dye doped polymers, were carried out. The interest in this type of holographic recording is due to the improved signal to noise ratio and the possibilities for image and signal processing, optical switch, beam steering, optical polarizers and selective erasure. We focused our investigation on the mechanisms that can possibly induce diffraction gratings in these different types of photosensitive materials, on the peculiarities of the achieved diffractive devices and on their possible applications. In particular we investigated the effects of polarization holography on azo-dye Langmuir-Blodgett films, on polymer dispersed liquid crystal (PDLC), and on liquid crystal films confined by dye-doped polymers aligning layers. In the first system, conventionally used for polarization holographic recording, we investigated the influence of the particular Langmuir-Blodgett deposition technique on the features of the recorded structures in order to obtain pure polarization gratings. The absence of surface reliefs gratings (SRG), the stability of the recorded devices and the high induced birefringence of the selected material, open up the possibility of interesting applications. In particular, we report the design and the implementation of a photopolarimeter for simultaneous measurements of Stokes parameters of light, in which the basic element is the actual polarization grating. PDLC is a non conventional system for polarization holographic recording, because no azocompounds are present in the polymeric and liquid crystalline mixtures. Polarization holographic storage produces diffraction gratings that originate mainly from the liquid crystal alignment inside the droplets of the solid polymeric matrix, created during the polymerization and phase separation processes. Polarization properties and electro-optical switching behaviour of the gratings are studied. We also report the unexpected observation of SRG in a system without azo compound, where photoisomerization and chromophore reorientation processes do not occur. In the last systems, we exploit a new method for spatially varying liquid-crystal alignment using patterned surfaces obtained by means of a polarization holographic exposure on a dye-doped polyimide. This idea is based on the fact that holographic gratings on some photosensitive material provide a periodic alignment of the nematic liquid crystals. In fact, putting in contact a Polarization holographic recording in polymeric and liquid crystalline materials ii thin film of liquid crystal with the aligning layers, we obtain a replica-grating in the bulk with the same properties of the gratings recorded on photosensitive layers. We describe the high flexibility of these replica-gratings, related to the control of the diffraction efficiency by means of an external electric field, and the very singular properties of the polarization states of the beams diffracted from this device. We also obtain two dimensional (2D) gratings consisting of a 2D array of differently twisted structures of nematic liquid crystal, achieved by a crossed assembling of polarization holograms recorded at the surfaces of the aligning substrates. These devices diffract the incident beam in several diffracted beams with various polarization states at the same time. The energy distribution can be controlled by means of the polarization state of the incident beam. Additionally, the distribution of the intensity on the diffracted beams can be completely controlled by means of a low external applied voltage. These features make the optical devices very interesting for beam steering, beam shaping and other modifications of light intensity or phase.
Dottorato di Ricerca in “Scienze e Tecnologie delle Mesofasi e dei Materiali Molecolari, Ciclo XIX, a.a. 2005-2006
Keywords: Fisica; Cristalli liquidi; Polimeri